2021
DOI: 10.1002/jssc.202100593
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the development of chiral stationary phases for high‐performance liquid chromatography

Abstract: Separations and analyses of chiral compounds are important in many fields, including pharmaceutical production, preparation of chemical intermediates, and biochemistry. High-performance liquid chromatography using a chiral stationary phase is regarded as one of the most valuable methods for enantiomeric separation and analysis because it is highly efficient, is broadly applicable, and has powerful separation capability. The focus for development of this method is the identification of novel chiral stationary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 226 publications
(243 reference statements)
0
27
0
Order By: Relevance
“…In 1980, Okamoto et al reported that the single‐handed helical poly(triphenylmethyl methacrylate) obtained by the helix‐sense‐selective anionic polymerization of triphenylmethyl methacrylate showed excellent chiral recognition abilities toward various racemic compounds when used as a CSP for HPLC 7–9 . Since then, a large variety of CSPs based on helical polymers with a preferred‐handed helical structures have been developed, some of which are commercially available 10–16 …”
Section: Introductionmentioning
confidence: 99%
“…In 1980, Okamoto et al reported that the single‐handed helical poly(triphenylmethyl methacrylate) obtained by the helix‐sense‐selective anionic polymerization of triphenylmethyl methacrylate showed excellent chiral recognition abilities toward various racemic compounds when used as a CSP for HPLC 7–9 . Since then, a large variety of CSPs based on helical polymers with a preferred‐handed helical structures have been developed, some of which are commercially available 10–16 …”
Section: Introductionmentioning
confidence: 99%
“…In the chiral HPLC, enantioseparation can be accomplished directly with a chiral stationary phase (CSP) and chiral mobile phase additive (CMPA) 5–10 . In recent years, more and more researchers have developed and used chiral columns, but they are of high price, poor stability, and have a comparatively short lifetime 11 . Moreover, because of its strong stereospecificity, the chiral HPLC column cannot be utilized widely 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] In recent years, more and more researchers have developed and used chiral columns, but they are of high price, poor stability, and have a comparatively short lifetime. 11 Moreover, because of its strong stereospecificity, the chiral HPLC column cannot be utilized widely. 11,12 On the other hand, the method of utilizing the CMPA has been widely used in exploratory research as a versatile and flexible method to demonstrate greater potential in chiral separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homochiral MOFs, due to their chiral properties and disposition, including enantiopure ligands or special helical topology architectures, are one of the host materials for the appropriate enantioselective separation of racemic drugs in the chemical and pharmaceutical industries [15][16][17]. Homochiral MOFs have attracted increasing attention to racemic drugs enantioseparation as chiral stationary phases (CSP) for HPLC [2,15,18], GC [19][20][21], and CEC [17,22] in recent years. Biologically derived ligands have proved successful in the synthesis of MOFs, such as dipeptides [23], tripeptides [24], nucleobases [25], and their derivatives [2,15], but the application of these homochiral MOFs in CEC for enantioseparation has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%